2015
DOI: 10.1590/0104-6632.20150323s00003133
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Dairy Wastewater Treated by Membrane Bioreactor and Nanofiltration: Technical and Economic Feasibility

Abstract: -This study evaluated the technical and economic feasibility of membrane bioreactors (MBR) followed by nanofiltration (NF) for dairy wastewater treatment in order to reuse the treated effluent. It was observed that the MBR efficiently removed the organic matter and color of the feed effluent; however, due to the high concentration of dissolved solids in the permeate, it was necessary to use nanofiltration as a polishing step. The final treated effluent could be reused in the industry for cooling, steam generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Studies have shown that at elevated TMP and flux, the membrane could easily polarize and the tendency for bio-flocs disintegration is high. This habitually resulted in excessive operational energy requirements [118][119][120]. The findings of the previous studies on MBR configurations are summarized in Table 2.…”
Section: Side-stream Configuration (Ss-mbr)mentioning
confidence: 99%
“…Studies have shown that at elevated TMP and flux, the membrane could easily polarize and the tendency for bio-flocs disintegration is high. This habitually resulted in excessive operational energy requirements [118][119][120]. The findings of the previous studies on MBR configurations are summarized in Table 2.…”
Section: Side-stream Configuration (Ss-mbr)mentioning
confidence: 99%
“…This could be attributed to the fact that the rejection of monovalent ions such as Na + by NF is weak. 42,43 In addition, the pH did not affect the membrane rejection when the polyamide membrane pH operating range is 4-11. Figure 7 shows the results of RO for waste water treatment containing cations and anions using the old RO and new RO membranes.…”
Section: Resultsmentioning
confidence: 92%
“…42 While the membrane separation systems and the combination of these systems with other technologies, such as membrane bioreactors (MBR), are the most promising treatment technologies for effluent reuse. 43 Also, studies show that NF is an efficient treatment system for secondary or tertiary effluents aiming at the generation of water for industrial, agricultural, or indirect potable reuse.…”
Section: Wastewatermentioning
confidence: 99%
“…The conventional treatments of wastewater generated in dairy industries include the use of primary treatment to remove solids and fats and biological treatment to eliminate organic matter and nutrients and in some cases tertiary treatment as polishing [3], [4], [7], and [8]. Among biological treatment methods which are commonly employed for dairy wastewater, sequencing batch reactor (SBR), up-flow anaerobic sludge blanket reactor, activated sludge plants and anaerobic treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among biological treatment methods which are commonly employed for dairy wastewater, sequencing batch reactor (SBR), up-flow anaerobic sludge blanket reactor, activated sludge plants and anaerobic treatment [9]. However, several problems have been reported, such as high production of scum, low sludge settleability and difficulties in removal of nutrients (nitrogen and phosphorus) [7]. In recent years several works demonstrated that application of MBR technologies were becoming more energy efficient as compared to conventional methods.…”
Section: Introductionmentioning
confidence: 99%